Automação do processo de furação de pequenas peças - Ribeiro, Fabiano (2014)
The research proposes a system for automating of the drilling of parts process, from the need for a branch company of machining. Motivated by the increase in productivity and the prevention of occupational accidents and diseases caused by repetitive efforts of operators, a proposal was developed using the programmable controller CLIC produced by WEG Automação. Substantiated by theoretical concepts of automation, programmable logic controllers and programming languages defined by IEC 61131-3, the work presents as a result of the logic of operation and functioning, and the program written in Ladder for application to the controller mentioned earlier. In the conclusion it is observed that with the implementation of the proposed objectives can be achieved interesting results for the company in question.